Ten myths about Calvinism : recovering the breadth of the Reformed tradition - Stewart, Kenneth J. (Downers Grove, Ill. : IVP Academic ; Nottingham, England : Apollos, 2011)
Ken Stewart identifies ten myths held by either or both Calvinists and non-Calvinists and shows how they are gross mischaracterizations of that theological stream. Certain of these persistent stereotypes that defy historical research often present a truncated view of the depth and breadth of the Reformed tradition. Others, although erroneous, are nevertheless used to dismiss outright this rich body of biblical theological teaching. --from publisher description.
One man (Calvin) and one city (Geneva) are determinative -- Calvin's view of predestination must be ours -- TULIP is the yardstick of the truly Reformed -- Calvinists take a dim view of revival and awakening -- Calvinism is largely antimissionary -- Calvinism promotes antinomianism -- Calvinism leads to theocracy -- Calvinism undermines the creative arts -- Calvinism resists gender equality -- Calvinism has fostered racial inequality -- Recovering our bearings: Calvinism in the twenty-first century.
Includes bibliographical references and indexes.
Keywords: Calvinism; Reformed Church -- Doctrines